2020
DOI: 10.1002/jsfa.10592
|View full text |Cite
|
Sign up to set email alerts
|

Role of sucrose in modulating the low‐nitrogen‐induced accumulation of phenolic compounds in lettuce (Lactuca sativa L.)

Abstract: BACKGROUND: Phenolic compounds are phytochemicals present in vegetables which contribute to human health. Although nitrogen deficiency and sucrose (Suc) are linked to phenolic production in vegetables, the relationship between them in the regulation of phenolic biosynthesis remains unknown. This study investigated the potential role of Suc in regulating phenolic biosynthesis of lettuce under low-nitrogen (LN) conditions. RESULTS: Our results showed that LN treatment significantly increased Suc content in lettu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…First, SPS and SS are the basic enzymes that enter the C metabolism pathway. The activities of the two enzymes are consistent with the changes in the content of sucrose, which clearly shows that the activities of SPS and SS are directly related to the synthesis of sucrose (Zhou et al, 2020). The accumulation pattern of starch in the leaves further validates the accumulation pattern of carbohydrates (Figs.…”
Section: Notesupporting
confidence: 74%
See 1 more Smart Citation
“…First, SPS and SS are the basic enzymes that enter the C metabolism pathway. The activities of the two enzymes are consistent with the changes in the content of sucrose, which clearly shows that the activities of SPS and SS are directly related to the synthesis of sucrose (Zhou et al, 2020). The accumulation pattern of starch in the leaves further validates the accumulation pattern of carbohydrates (Figs.…”
Section: Notesupporting
confidence: 74%
“…Previous studies have revealed that mineral nutrients further regulate the activities of key enzymes such as PAL, C4H and 4CL (Li et al, 2021). The reduction in N levels can directly promote carbohydrate content and quickly activate the activity of flavonoid-metabolizing enzymes (Zhou et al, 2020). Throughout the process, these ammonium ions released from the PAL pathway are generated by the GS/GOGAT assimilation system to produce glutamate, which provides an amino donor for phenylalanine regeneration and N cycle completion (Singh, Lewis & Towers, 1998), thereby affecting the biosynthesis of flavonoids.…”
Section: Notementioning
confidence: 99%
“…The synergistic effects of high soluble sugars (especially sucrose) and low N on anthocyanin production in the presence of light have been demonstrated in numerous plant systems (e.g. Lea et al ., 2007; Boussadia et al ., 2010; Su et al ., 2016; Zhou et al ., 2020), and appear to result from upregulation of multiple independent transcription factors related to anthocyanin synthesis (e.g. PAP1 and PAP2), which together result in greater anthocyanin synthesis than individual stimuli alone (Lea et al ., 2007).…”
Section: Autumn Leaf Colors: Proximate Vs Ultimate Causationmentioning
confidence: 99%
“…Due to their antioxidant, anti‐inflammatory, and antitumoral effects, various human health benefits have been reported (Kang et al, 2018 ). Phenolic compounds such as phenolic acids and flavonoids are phytochemicals widely distributed in leafy vegetables and are also considered compounds with antioxidant properties (Negrao et al, 2021 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%